Combination of nitric oxide and 1-MCP on postharvest life of the blueberry (Vaccinium spp.) fruit - Gergoff Grozeff, Gustavo Esteban (2017)
Blueberries are a perishable fruit that loses its firmness and weight rapidly after harvest. High concentrations of ascorbic acid (AA) and phenolic compounds such as anthocyanins are important attributes contributing to the quality of the fruit. The aim of this work is to extend the postharvest life of three blueberries cultivars; ‘Mistý and ‘Blue Cuinex́, firm and soft cultivars respectively and ‘Blue Chiṕ with intermediate firmness. The fruit was treated separately or in combination with a nitric oxide donor, S-nitrosoglutathione (GSNO) and 1-methylcyclopropene (1-MCP) and stored at 4 °C for 14 d. The best treatment for ‘Blue Cuinex́ was the combination of 1- MCP and GSNO, while ‘Mistý softened slower when treated with 1-MCP, and ‘Blue Chiṕ was not affected by treatment. The 1-MCP+ GSNO treatment maintained higher concentrations of AA and GSH in ‘Blue Cuinex́. AA concentrations declined in ‘Mistý but did not respond to GSNO. The combination of 1-MCP and GSNO extended the postharvest life of ‘Blue Cuinex́ by improving the concentrations of AA and glutathione in the berries but not for ‘Mistý. These results demonstrate that blueberry cultivars respond differentially to 1-MCP and nitric oxide, and that the sequence of application could be used to slow fruit softening and maintain antioxidant properties.